FORECASTING DEMAND MENGGUNAKAN MODEL ARIMA PADA PEMAKAIAN AIR BERSIH PRODUKSI PDAM KABUPATEN KEDIRI - Nurhidayat, Tesya Iqbal; Kurniawan , Rony (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this research to forcast the short term of usage clean water at the local water company (PDAM) Kabupaten Kediri by using the model Autoregressive Integrated Moving Average (ARIMA). The data usage is clean water usage data from September 2020 to May 2022 with a quantitative descriptive approach. While data processing using software E-Views 10 application. The result of this research indicated that model ARIMA (5,1,0) as the best model for forcasting the next 7 months clean water usage at PDAM Kabupaten Kediri which produces a positive trend pattern and tends to rise every month from juny – december 2022 in a row berturut 239672 m3, 2377734 m3, 238403 m3, 240608 m3, 240427 m3, 241039 m3, 243185 m3.